Quantitative Equity : Combining Value, Quality and Momentum - Krampera, Tomáš; Fičura, Milan; Janda, Karel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
Thesis focuses on backtesting equity factor portfolios in systematic model based way. Analysis usesextensive data libraries of CRSP and Compustat creating liquid and tradeable stock universe coveringUS equity market over 1981-2018. Analysis builds three long only portfolios based on value, qualityand momentum and study their performance and relationships. Multi-style portfolios are createdusing mix and integrated approaches. It is found that all long only standalone portfolios add value inexcess of market benchmark but taking away market exposure, the do not provide significant value.Long short standalone portfolios do not perform well in terms of risk-adjusted returns. Integratedmulti-style portfolios outperform mix portfolios benefiting from more efficient factor exposure. Ingeneral, multi-style portfolio outperform original standalone portfolios including long short versions.The core equity strategy, integrated combination of value, quality and momentum, provides the bestjob in outperforming the market but its outperformance is not superior enough to make it stand outover other multi-style portfolios.
Vedoucí práce: Milan Fičura
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses